ORGANIC GEOCHEMISTRY, PETROGRAPHY AND MINERALOGY OF WUNGKAL-GAMPING MUDSTONE IN BAYAT AREA, KLATEN, CENTRAL JAVA - , Noviar ([Yogyakarta] : Ikatan Ahli Geologi Indonesia, 2008)
The Geology of Bayat Area in Klaten, Central Java, which is regionally part of Southern Mountain, is very interesting to be researched. Near Pendul Hill, Bayat, dark grey mudstone of Wungkal-Gamping Formation can be found. The color of mudstones indicates that this mudstone is probably rich in organic contents and has potential to be a source rocksof hydrocarbon. This research has objectives to know how much organic material contained in Wungkal-Gamping mudstone and its potential to be source rock of hydrocarbon. TOC analysis and organic petrography analysis has been done to attain that objectives. TOC analysis result shows that 8 samples of mudstone in research area have range of 0.16 % to 0.42 % weight of TOC. Organic petrography analysis also shows that the organic materials occured in each sample are not more than 6 % volume. This results conclude that mudstone in research area does not have potential to be source rock of hydrocarbon. Organic petrography using spore fluorescence color analysis, shows that sporinite in rock sample has moderate orange to red or brown color which is equivalent with Ro of aprroximately 0.6 &ndash